Analisis Rasio Profitabilitas Dan Solvabilitas Pada PT. Ace Hardware Indonesia Tbk. Tahun 2018-2022 - Dewi Oktavia; Syifa Pramudita Faddila (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2023)
Financial statements are reports that show the financial condition of a company at a certain time or period of time. This study aims to determine the performance of PT. Ace Hardware Indonesia Tbk. by using profitability and solvency ratios. this study uses qualitative description analysis techniques, namely data in the form of numbers which include the company's financial statements that describe real conditions or conditions. The results showed that the company's performance from the calculation of the profitability ratio, namely the value of NPM, ROA and ROE, was calculated below the industry standard, it was concluded that the company experienced poor financial performance and experienced a decrease every year, while the calculation of the solvency ratio, namely the calculation of the year period From 2018 to 2022 the Dept To Assets Ratio (DAR) value has an average value of 21.9% and the Dep To Equity Ratio (DER) is 28.3%, it can be seen that the company is in good condition with average yields below the industry standard value , where the company is able to increase the value of assets and also capital to pay off the company's debt.